1993
DOI: 10.1159/000110319
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study on the Environmental Risk Factors of Parkinson's Disease in Tianjin, China

Abstract: Using a case-control method, we studied the role of environmental risk factors and viral infection in the development of Parkinson''s disease (PD) in China. Ninety-three PD patients and 186 controls were investigated with a questionnaire and from most of them, blood was taken to test the antibody levels of four virus (measles, rubella, HSV-1, CMV) IgG. The study result showed that positive family history, living near rubber plants, drinking river-water were associated with an increased risk of developing PD. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 12 publications
2
61
0
1
Order By: Relevance
“…and printing plants, observed no association with PD for any variable [146]. Another study found an excess risk following exposure to chemical substances, such as methanol, toluene, cyanide, mercury or petroleum products (OR 5.87, 95% CI 1.48-27.23) [145].…”
Section: Other Chemicalsmentioning
confidence: 95%
See 4 more Smart Citations
“…and printing plants, observed no association with PD for any variable [146]. Another study found an excess risk following exposure to chemical substances, such as methanol, toluene, cyanide, mercury or petroleum products (OR 5.87, 95% CI 1.48-27.23) [145].…”
Section: Other Chemicalsmentioning
confidence: 95%
“…Another case-control study found no association between residential exposure to paint plants and PD (OR 3.0, 95% CI 0.20-45.7) [146]. The only published prospective study reported no association between organic solvents and PD [330].…”
Section: Organic Solventsmentioning
confidence: 96%
See 3 more Smart Citations